Training, specialization ano ethical capacity, requirements for an integrating journalism in the knowledge society - Gutiérrez Atala, Fernando José (2009)
This work examines the specialization process that goes through the journalism profession. Nowadays, specialized knowledge leads the journalism through fragmentation and search of the necessary competences to face a reality that is not only complex but also aromized. This reality needs a meticulous and specific work. For this reason, the analysis tries to establish the specialized training not only as a technique necessity, but also asan ethical obligation for the journalist that wants ro respond the more and more speciftc audience s demands. This way: Itcould perform its last function executing an integrated role with the pubiic, giving the knowledge to the society.